Activation of Wnt3a signaling promotes myogenic differentiation of mesenchymal stem cells in mdx mice - Shang Yan-chang; Wang Shu-hui; Xiong Fu; Peng Fu-ning; Liu Zhen-shan; Geng Jia; Zhang Cheng (Acta Pharmacologica Sinica, 2017)
Aim: Duchenne muscular dystrophy (DMD) is an X-linked genetic muscular disorder with no effective treatment at present. Mesenchymal stem cell (MSC) transplantation has been used to treat DMD, but the efficiency is low. Our previous studies show that activation of Wnt3a signaling promotes myogenic differentiation of MSCs in vitro. Here we report an effective MSC transplantation therapy in mdx mice by activation of Wnt3a signaling. Methods: MSCs were isolated from mouse bone marrow, and pretreated with Wnt3a-conditioned medium (Wnt3a-CM), then transplanted into mdx mice. The recipient mice were euthanized at 4, 8, 12, 16 weeks after the transplantation, and muscle pathological changes were examined. The expression of dystrophin in muscle was detected using immunofluorescence staining, RT-PCR and Western blotting. Results: Sixteen weeks later, transplantation of Wnt3a-pretreated MSCs in mdx mice improved the characteristics of dystrophic muscles evidenced by significant reductions in centrally nucleated myofibers, the variability range of cross-sectional area (CSA) and the connective tissue area of myofibers. Furthermore, transplantation of Wnt3a-pretreated MSCs in mdx mice gradually and markedly increased the expression of dystrophin in muscle, and improved the efficiency of myogenic differentiation. Conclusion: Transplantation of Wnt3a-pretreated MSCs in mdx mice results in long-term amelioration of the dystrophic phenotype and restores dystrophin expression in muscle. The results suggest that Wnt3a may be a promising candidate for the treatment of DMD.